2013
DOI: 10.1016/j.dci.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Newcastle disease virus vaccine antibodies on the shedding and transmission of challenge viruses

Abstract: Different genotypes of avian paramyxovirus serotype-1 virus (APMV-1) circulate in many parts of the world. Traditionally, Newcastle disease virus (NDV) is recognized as having two major divisions represented by classes I and II, with class II being further divided into sixteen genotypes. Although all NDV are members of APMV-1 and are of one serotype, antigenic and genetic diversity is observed between the different genotypes. Reports of vaccine failure from many countries and reports by our lab on the reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 36 publications
6
116
0
5
Order By: Relevance
“…Currently used vaccines against respiratory pathogens are not always protective in field situations. Possible explanations for vaccine failure include infection with heterologous viruses and inadequate storage or application of the vaccine (de Wit et al, 2010, Dortmans et al, 2012, Miller et al, 2013. For the development of novel vaccines, more information is needed on deposition and subsequent uptake by APC after mucosal application of a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Currently used vaccines against respiratory pathogens are not always protective in field situations. Possible explanations for vaccine failure include infection with heterologous viruses and inadequate storage or application of the vaccine (de Wit et al, 2010, Dortmans et al, 2012, Miller et al, 2013. For the development of novel vaccines, more information is needed on deposition and subsequent uptake by APC after mucosal application of a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…While according to Hu et al (2011), the NDV still found in vaccinated chickens because of the shedding of vaccine virus which not homologous with field virus. This was evidenced by Miller et al (2013) experimentally by vaccinating chickens with LaSota vaccine, and then the chickens were challenged with heterologous virulent NDV (CA/2002) which different genotype with the vaccine virus and the result showed the challenge virus was still excreted into environment and infect unvaccinated chickens (control). According to Miller et al (2013) using homologous vaccine with field virus may decrease excretion of virus into environment more than heterologous vaccine.…”
Section: Isolation Of Ndv In Spf Embryonated Chicken Eggsmentioning
confidence: 99%
“…This was evidenced by Miller et al (2013) experimentally by vaccinating chickens with LaSota vaccine, and then the chickens were challenged with heterologous virulent NDV (CA/2002) which different genotype with the vaccine virus and the result showed the challenge virus was still excreted into environment and infect unvaccinated chickens (control). According to Miller et al (2013) using homologous vaccine with field virus may decrease excretion of virus into environment more than heterologous vaccine. Most of ND vaccine not prevent vaccinated birds from virulent NDV infection but vaccination significantly may decrease the amount of virus excreted through saliva and feces compared to unvaccinated birds (Kapczynski & King 2005;Miller et al 2009).…”
Section: Isolation Of Ndv In Spf Embryonated Chicken Eggsmentioning
confidence: 99%
“…ND is a devastating viral disease of avian species that results in high mortality and morbidity (Miller et al 2013). NDV infects a wide range of birds with varying susceptibilities.…”
Section: Serological Examinationmentioning
confidence: 99%
“…These are multi-factorial problem in poultry, with viral and bacterial respiratory pathogens often concurrently present and most probably influencing one another (Marien et al 2006). Newcastle disease virus (NDV) and Mycoplasma gallisepticum (MG) are two economically most important pathogens affecting respiratory system of poultry birds (Miller et al 2013, Aguero et al 2015Zia et al 2017a).…”
Section: Introductionmentioning
confidence: 99%